Implementasi Pengesahan Badan Hukum Yayasan Pendidikan (Perspektif Undang-Undang Nomor 28 Tahun 2004 Tentang Perubahan Atas Undang-Undang Nomor 16 Tahun 2001 Tentang Yayasan) (Lex Jurnalica, 2010)
In Indonesia, one of the factors that make worse the image of education (especially private education) are still many people who establish  foundation of education just to take their own profit without maintaining of their output of it. The purpose of the establishment of the foundations which are originally  social term, then  they  are turned into abuse of some owners  because of lacking of education understanding. Before 2001 in Indonesia, esta-blishment foundations were only based on society  habits and the jurisprudence of the Supreme Court, because there was no rule about it. The facts shows that people found foundations in order to be concealed behind its status  which are not only used as a place to develop social activities, religious, humanitarian, but sometimes it also aimed to enrich themselves (founders, managers and supervisors).  In line with these trends,  then many pro-blems arise, they are related to incompatible foundation activities with intentions and purposes stated in basic budget. Establishment of the foundation is legalized by notarial deed and  then it approved by Minister of Law and Human Rights .It is intended to manage administrative arrangements of endorsement of a foundation as a legal entity ,well. It is important to prevent establishment of the foundation inapropriate way, based on any rule and regulation, procedurall .Keywords: Foundations, Education, Legal Entities